2022
DOI: 10.3390/v14102200
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Viral RNA-Dependent RNA Polymerases: Insights from Recent Structural Studies

Abstract: RNA-dependent RNA polymerases (RdRPs) represent a distinctive yet versatile class of nucleic acid polymerases encoded by RNA viruses for the replication and transcription of their genome. The structure of the RdRP is comparable to that of a cupped right hand consisting of fingers, palm, and thumb subdomains. Despite the presence of a common structural core, the RdRPs differ significantly in the mechanistic details of RNA binding and polymerization. The present review aims at exploring these incongruities in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…The NSP12 of SARS-CoV-2 (PDB: 7BV2, [87]) consists of the interface domain (residues 251-365), the RdRp domain, and the N-terminal nidovirus RdRp-associated nucleotidyltransferase domain (NiRAN, residues 117-250) [88]. The core polymerase comprises the thumb subdomain, the palm subdomain, and the finger subdomain and is involved in the pivotal function of genome replication and transcription [89,90]. Earlier studies have indicated the role of various residues such as E254D, A423V, A656S, V720I, and V776L in NSP12, S25L and M75I, in NSP7 and the NSP8 mutation T145I in polymerization [91,92].…”
Section: Mutational Analysis Of Nsp 7-8-12mentioning
confidence: 99%
“…The NSP12 of SARS-CoV-2 (PDB: 7BV2, [87]) consists of the interface domain (residues 251-365), the RdRp domain, and the N-terminal nidovirus RdRp-associated nucleotidyltransferase domain (NiRAN, residues 117-250) [88]. The core polymerase comprises the thumb subdomain, the palm subdomain, and the finger subdomain and is involved in the pivotal function of genome replication and transcription [89,90]. Earlier studies have indicated the role of various residues such as E254D, A423V, A656S, V720I, and V776L in NSP12, S25L and M75I, in NSP7 and the NSP8 mutation T145I in polymerization [91,92].…”
Section: Mutational Analysis Of Nsp 7-8-12mentioning
confidence: 99%
“…RdRp, a commonly conserved component of RNA viruses, is widely used as a target for antiviral drug screening [10]. Sofosbuvir is approved for the treatment of hepatitis important role in the replication and transcription of ZIKV and is absent in human beings, it has been proposed as a potential drug target for anti-ZIKV agents [9].…”
Section: Introductionmentioning
confidence: 99%
“…RdRp, a commonly conserved component of RNA viruses, is widely used as a target for antiviral drug screening [10]. Sofosbuvir is approved for the treatment of hepatitis C virus infection, primarily targeting RdRp.…”
Section: Introductionmentioning
confidence: 99%
“…RdRps' right hand is closed and they share a common core architecture with 7 highly conserved motifs named A to G (2,3). The detailed structure of RdRps has been largely discussed elsewhere (2,(4)(5)(6) and the structural overview presented here only provides the minimal background to discuss the impact of phosphorylation sites.…”
Section: Introductionmentioning
confidence: 99%